Impact of COVID-19 on chronic respiratory disease outcome survey in Pakistan - Alishba Malik, Umar Ejaz, Kaneez Uma Farva Kousar, Muhammad Kashif Bashir, Faheem Ahmed Memon, Muhammad Naeem (Pakistan Journal of Medical & Health Sciences, 2022)
Introduction: Pakistan has high prevalence of chronic respiratory diseases, especially bronchial asthma and chronic obstructive pulmonary disease (COPD). Objectives: The main objective of the study is to find the impact of COVID-19 on chronic respiratory disease in Pakistan. Material and methods: This cross sectional study was conducted in King Edward Medical University, Mayo Hospital Lahore during January 2021 to July 2021. Before and after the COVID-19 period were defined by a predetermined set of criteria in the form of a questionnaire. Results: The data was collected from 314 respondents. According to the respondents, the survey also queried about the presence of respiratory comorbidities in patients who had tested positive for COVID 19. COPD was mentioned as a comorbidity by more than a third of those who responded, and several others, including bronchial asthma, ILD, and tuberculosis (TB), were also mentioned by many respondents. Conclusion: It is concluded that because of the lockout’s efficacy and the widespread use of masks outside the facility, the air was probably rather clean. As a result, both the number of people visiting an asthma outpatient clinic and the number of people being admitted to the hospital with acute severe asthma dropped.